ATF3/EGR1 regulates myocardial ischemia/reperfusion injury induced autophagy and inflammation in cardiomyocytes: ATF3/EGR1 control heart injury via autophagy & inflammation - Li, Li; Fu, Gang; Liu, Caiyun; Liu, Yanling (Cellular and Molecular Biology, 2024)
Myocardial ischemia/reperfusion injury (MIRI) is an irreversible adverse event during the management of coronary heart disease that lacks effective controls. The underlying mechanism of MIRI still requires further investigation. Recent studies have suggested that overexpression of ATF3 protects against MIRI by regulating inflammatory responses, ferroptosis, and autophagy. The downstream target of ATF3, EGR1, also showed cardioprotective properties against MIRI by promoting autophagy. Therefore, further investigating the effect of ATF3/EGR1 pathway on MIRI-induced inflammation and autophagy is needed. Cardiomyocyte MIRI model was established by challenging H9C2 cells with hypoxia/reoxygenation (H/R). The ATF3 overexpression-H/R cell model by transfecting ATF3 plasmid into the H9C2 cell line. The transcription levels of ATF3 and EGR1 were determined using RT-qPCR, the levels of TNF-α and IL-6 were determined using ELISA kits, the protein expression of LC3 I, LC3 II, and P62 was determined via WB, and microstructure of H9C2 cell was observed by transmission electron microscopy (TEM). Overexpression of ATF3 significantly downregulated Egr1 levels, indicating that EGR1 might be the target of ATF3. By upregulating ATF3 levels, the extracellular levels of the inflammatory cytokines TNF-α and IL-6 significantly decreased, and the protein expression of the autophagy markers LC3 I, LC3 II, and P62 significantly increased. TEM results revealed that the cell line in the H/R-ATF3 group exhibited a higher abundance of autophagosome enclosures of mitochondria. The results indicated that ATF3/EGR1 may alleviate inflammation and improve autophagy in an H/R-induced MIRI model of cardiomyocytes.